Development of autonomous lane following and collision avoiding robot using image processing - Fazili, Atif; Ul Imaan, Diyan; Rashid, Muhammad Mahbubur (2012)
The proposed robot, as the name suggests has the ability to navigate autonomously in between lanes using a camera as its vision and will also avoid collision in the forward direction with the aid of an Infra Red sensor. All the computations in this research are handled by Atmel Mega644 Microcontroller Unit (MCU). A RC (Radio controlled) car is chosen and modified to suit this needs. The RC car provides all the components and infrastructure necessary for a simple mechanical system, all at a low cost with an easy-to-use interface. Using an IR distance sensor, the car determines when to stop accelerating once a certain distance between a forward object has been breached. Due to the nature of the input peripherals, especially the camera, computations had to be optimized as much as possible in order for the car to be able to react and respond with proper movements in real time. In addition, given the limited computational capacity of this 8-bit MCU (microcontroller unit), our design made use of several computational efficiency strategies as is explained in details in the paper.